2019
DOI: 10.1002/ajp.22989
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in wild and captive Guizhou snub‐nosed monkeys, Rhinopithecus brelichi

Abstract: Many colobine species-including the endangered Guizhou snub-nosed monkey (Rhinopithecus brelichi) are difficult to maintain in captivity and frequently exhibit gastrointestinal (GI) problems. GI problems are commonly linked to alterations in the gut microbiota, which lead us to examine the gut microbial communities of wild and captive R. brelichi. We used high-throughput sequencing of the 16S rRNA gene to compare the gut microbiota of wild (N = 7) and captive (N = 8) R. brelichi. Wild monkeys exhibited increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
94
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 115 publications
14
94
2
Order By: Relevance
“…We also observed a significant increase in the relative abundance of Prevotella_1 in domestic horses, which may be associated with high-grain diet and contribute to fiber, carbohydrate, simple sugar, or tannin degradation (Wu et al, 2011;Li et al, 2013) in captive horses (Fernando et al, 2010). Prevotella abundance was similarly elevated in captive monkeys (Hale et al, 2018), but other mammal studies reported conflicting results (Mckenzie et al, 2017). Given the role of diet in shaping the gut microbiome, especially those related to microbial fermentation in horses, the variation in abundance of bacteria under the same diet indicate that the composition of the microbiomes is not influenced by diet passively.…”
Section: Discussionmentioning
confidence: 55%
“…We also observed a significant increase in the relative abundance of Prevotella_1 in domestic horses, which may be associated with high-grain diet and contribute to fiber, carbohydrate, simple sugar, or tannin degradation (Wu et al, 2011;Li et al, 2013) in captive horses (Fernando et al, 2010). Prevotella abundance was similarly elevated in captive monkeys (Hale et al, 2018), but other mammal studies reported conflicting results (Mckenzie et al, 2017). Given the role of diet in shaping the gut microbiome, especially those related to microbial fermentation in horses, the variation in abundance of bacteria under the same diet indicate that the composition of the microbiomes is not influenced by diet passively.…”
Section: Discussionmentioning
confidence: 55%
“…These NHP species also have altered gut microbiome composition, with increased relative abundances of genera such as Bacteroides in captivity. Studies with black howler monkeys ( A. pigra ; Amato et al, ; Nakamura et al, ) and snub‐nosed monkeys ( Rhinopithecus bieti ; Hale et al, ) demonstrate similar patterns. Nevertheless, all of these studies focus on leaf‐eating NHPs, and a dearth of data exists for NHPs with more generalist diets.…”
Section: Introductionmentioning
confidence: 89%
“…Within a research setting, we observed that increased levels of captivity of indoor-only standardized cage housing when compared to indoor-outdoor lifestyle reduced alpha diversity of GI microbiota, albeit modestly. Previous literature has reported a similar trend of reduced diversity between NHPs in captivity, or semi-captive lifestyles compared to those in the wild, although the changes were primarily attributed to dietary adaptations (27, 45). Our study shows that, within a diet-controlled setting, indoor housing is associated with a trend of reduced microbial diversity, overt bacterial community richness differences, and modest taxonomic disruptions within captive-born SMs.…”
Section: Discussionmentioning
confidence: 54%